AB1416-HPR A REVIEW OF PUBLIC PATIENT INVOLVEMENT AND ENGAGEMENT (PPI/E) AT THE ARTHRITIS RESEARCH UK CENTRE FOR ADOLESCENT RHEUMATOLOGY AT UCL, UCLH AND GOSH. (June 2019) - Wilton, James; Clifford, Caitlin; Chaplin, Hema; Eleftheriou, Despina; Radziszewska, Anna; Ciurtin, Coziana; Robinson, George; Martin-Gutierrez, Lucia; Sen, Debajit
Abstract : Background: The adolescent and young adult (AYA) rheumatology clinical service has a well established culture of involving our users in shaping how services are delivered. Since its inception in 2012 the Arthritis Research UK Centre for Adolescent Rheumatology has worked to offer every patient within the clinical service the opportunity to participate in research Objectives: This was achieved by 2015 and from 2014 we renewed our focus on an active involvementprogramme to promote the role of young people in prioritising and designing our research agenda and workstreams. We are currently developing our strategy for the next five years and reviewing our experience to date. Methods: PPI/E activity records were searched for the period October 2014 to April 2018. This included number of patients involved, their age and diagnosis, and the type of activity along with the number of times they have been involved. Results: 19 PPI/E activities were organised. From a total of 1554 adolescent and young adult patients 150 patients having been involved in PPI/E, the age range was 11-27 and 118 were female. The activities consisted of focus groups (79%) and support days (11%) all but two of which were disease specific groups. The disease specific PPI/E activities have been focused on JIA, JSLE, and JDM. The number of patients involved in these activities were 24.62% (n=99), 24% (n=17) and 66% (n=25) respectively. The mean instances of involvement per disease were 2.09 for JIA, 2.53 for JSLE and 3.56 for JDM. Conclusion: Our results show that many of our patients have taken part in PPI/E activities (11.19%) with over 65% of of our JDM patients having taken part in either a focus group or support day. The focus on inflammatory rheumatic disease is in keeping with the stated aims of our Centre. The mean instances of involvement ranging from 2.09 3.56 suggest that patients feel PPI/E is worthwhile. We aim to share our results with the young people who have driven this work and will consider how we might move forward. We aim to consult with the group of patients we serve who have not been part of this process to date. Disclosure of Interests: None declared